Bioinsecticidal Activity of Cerbera odollam Gaertn. Leaf Extract Against Thrips parvispinus Karny on Cayenne Pepper (Capsicum frutescens L.) - Sri Ambardini; Eva Indraswari; Jendri Mamangkey; La Ode Adi Parman Rudia (International Journal of Science and Environment (IJSE), 2026)
The increasing reliance on synthetic insecticides for pest management has raised concerns regarding environmental contamination, pest resistance, and adverse effects on non-target organisms. Consequently, the development of environmentally friendly alternatives such as botanical insecticides has gained considerable attention. This study aimed to evaluate the effectiveness of Cerbera odollam Gaertn. leaf extract against Thrips parvispinus Karny and to determine the lethal concentration required to kill 50% of the test population (LC₅₀) within 96 h of exposure. The experiment was conducted from August to October 2021 at the Biology Laboratory and Greenhouse, Faculty of Mathematics and Natural Sciences, Halu Oleo University, Indonesia. A Completely Randomized Design (CRD) was employed consisting of four extract concentrations, namely 1.0%, 1.5%, 2.0%, and 2.5%, along with a positive control (Regent 50 SC) and a negative control (distilled water). The extract was applied by spraying onto cayenne pepper plants infested with T. parvispinus, and observations were carried out for seven consecutive days. Mortality percentage, mortality rate, and LC₅₀ values were evaluated. The results demonstrated that C. odollam leaf extract significantly increased thrips mortality. The highest efficacy was observed at a concentration of 2.5%, resulting in 100% mortality and a mortality rate of 0.55 individuals per 24 h, which was statistically comparable to the positive control treatment. Probit analysis revealed an LC₅₀ value of 2.07% after 96 h of exposure. These findings indicate that C. odollam leaf extract possesses considerable potential as an environmentally sustainable botanical insecticide for controlling T. parvispinus populations in cayenne pepper cultivation.